Circulating endothelial cells and serum visfatin are indicators of cardiovascular disease risk in psoriasis patients - Lamia Elgarhy; Naeim Abdelnabi; Amani Abdullatif; Mohamed Attia; Maaly Mohammad Mabrouk; Eman El Sheikh (Wolters Kluwer Medknow Publications, 2016)
Background: Cardiovascular risk in psoriasis (PS) appears to be dependent on disease severity. Circulating endothelial cell (CEC) counts appear to be elevated in numerous conditions associated with endothelial dysfunction including chronic immune-mediated inflammatory disorders. Adipokines could serve as a missing link between PS and comorbidities Aim: To evaluate the numbers of CECs and serum visfatin levels in PS patients in comparison to controls to investigate their possible role in increased cardiovascular disease (CVD) risk. Methods: Twenty-five PS patients and 15 healthy individuals were recruited. CECs numbers were detected in peripheral blood samples through studying CD146 and CD45 expression by flow cytometry. Serum visfatin levels were detected by enzyme-linked immunosorbent assay. Results: There was a statistically significant increase in CEC numbers and serum visfatin levels in PS patients compared to controls (p < 0.001) with significant positive correlations between serum visfatin levels and PS severity and numbers of CECs in PS patients. Also, there was a significant difference in numbers of CECs (p ≤ 0.001) and serum visfatin levels (p ≤ 0.001) between CVD risk positive and CVD risk negative psoriasis patients. Conclusion: Both numbers of CECs and serum visfatin levels were increased in PS patients compared with controls and also increased in CVD risk positive when compared with CVD risk negative PS patients. Both correlated with disease severity suggesting the possibility of increased CVD risk in PS patients.